PENGARUH JUMLAH BIBIT PERLUBANG TANAM TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS PADI SAWAH - Fathul Bahri; Radian Radian; Wasi’an Wasi’an (Partner, 2021)
Overcoming food problems, it is necessary to have a break through to increase the productivity of rice plants by utilizing the available paddy fields through emphasizing the application of technological innovations in the Integrated Crop Management approach. In the application of technological innovation, the Integrated Crop Management approach is not only carried out using varieties but must be followed by correct cultivation techniques following the recommendations for the application of technology. This study used a randomized block design (RBD) method with the results of the age of 15 DAS had a very significant effect on the treatment of varieties, while the age of 35.45 DAS and the increase in tillers aged 25 DAS had an interaction. Thus, the number of perforated seeds did not have a significant effect on the growth and yield of rice plants. Keywords: Variety, Number of Seeds, Rice